Student Voter Preferences Wiralodra University Indramayu 2012 - Dewi Nurmala Sari (Public Policy: Jurnal Ilmu Sosial dan Kebijakan, 2025)
After the 1998 Reformation movement, Indonesia experienced a transition process involving political institutionalization as an effort to consolidate democracy and decentralize government. The transition process has produced several positive things for the Indonesian nation, including increasing people's political participation. The researcher wanted to see the preferences of voters among students at Wilalodra University Indramayu. Voting behavior can be shown in voting and determining who will be elected as a public official in the election. Voting in the election is realized by voting for the political party they support or is shown by the behavior of the community in choosing a pair of legislative and executive candidates such as President/Vice President, Regent/Vice Regent or Mayor/Vice Mayor.